2012
DOI: 10.1186/1743-422x-9-270
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 gene polymorphisms and severity of pandemic A/H1N1/2009 influenza in otherwise healthy children

Abstract: BackgroundToll-like receptors (TLRs) form an essential part of the innate immune system, which plays a fundamental role in rapidly and effectively controlling infections and initiating adaptive immunity. There are no published data concerning the importance of polymorphisms of TLRs in conditioning susceptibility to influenza or the severity of the disease. The aim of this study was to evaluate whether selected polymorphisms of TLR2, TLR3 and TLR4 influence the incidence and clinical picture of pandemic A/H1N1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 34 publications
2
66
0
2
Order By: Relevance
“…In contrast, TLR3−/− mice have no survival advantage when infected with a 2009 pandemic H1N1 virus (Leung et al, 2014). A common polymorphism in the TLR3 gene has been associated with severe disease upon infection with 2009 pandemic H1N1 virus (Esposito et al, 2012). Thus, TLR3 may contribute to either pathogenesis or viral suppression during IAV infection of the alveoli.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, TLR3−/− mice have no survival advantage when infected with a 2009 pandemic H1N1 virus (Leung et al, 2014). A common polymorphism in the TLR3 gene has been associated with severe disease upon infection with 2009 pandemic H1N1 virus (Esposito et al, 2012). Thus, TLR3 may contribute to either pathogenesis or viral suppression during IAV infection of the alveoli.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated that TLR3 also contributes to pulmonary damage through the induction of pro-inflammatory molecules and the recruitment of leukocytes, during IAV virus infection [7, 4246]. Furthermore, TLR3 polymorphisms have been shown to be related to severe cases of influenza infection in humans and mice [42, 47, 48] and its upregulation has been associated with severe pulmonary lesions in the ferret model after IAV infection [42, 4649]. Moreover, it is known that TLR3 signalling is not required for the initial cell-autonomous recognition of viral infection or the induction of IFNα, which is induced via viral recognition by RIG-I [50].…”
Section: Discussionmentioning
confidence: 99%
“…Several potential genetic determinants associated with A(H1N1)pdm09 infection have been described, including TNF (Antonopoulou et al, 2012), IFN-inducible transmembrane (Everitt et al, 2012), killer-cell immunoglobulin-like receptor (Aranda-Romo et al, 2012), complement regulatory protein CD55 (Zhou et al, 2012) and Toll-like receptor 3 (Esposito et al, 2012). Data relating to the role of chemokine receptor 5 (CCR5) in severe A(H1N1)pdm09-infected patients are contradictory and have been debated (Keynan et al, 2010;Rodriguez et al, 2013;Sironi et al, 2014).…”
mentioning
confidence: 99%